The rules of faith for Rabbi Musa Bin Maimon through his book "Siraj uldarseen" and the extent of Islam’s influence on them - Al-maaitah, Qaiss (Jordan Journal of Islamic Studies, 2023)
This study comes to talk about an important dialectical figure and one of the great Jewish philosophers who appeared in the Middle Ages, and he lived within the confines of Islam, who is Musa bin Maimon, who is considered by the Jews to be among their great scholars and thinkers, but the study of the thought of Moses bin Maimonides finds that he was influenced by the scholars and philosophers of Islam and most of them Ibn Rushd The one who was influenced by his thought, and I will try in this study to prove that the rules of faith mentioned by Ibn Maimonides in his book “AlSiraj” were mostly derived from Islamic thought and philosophers and that many of these rules contravened the origins of the Jews in the Torah and the Talmud, so the researcher will mention the rule and then to prove the influence of Islam on him. Perhaps one of the most important findings of the research is to prove the tolerance of Islam in dealing with people of other religions and the freedom of belief and freedom of thought that existed in the educated and conscious Muslim society, and the personality study of Musa bin Maimonides is a guide and a realistic proof of this fact.